Daddy-Long-Legs - Webster, Jean, 1876-1916. (New York : Knopf, 1993)
A seventeen-year-old orphan is sent to a posh northeastern college for women by an anonymous benefactor. All she must do is write to the man she nicknames Daddy-Long-Legs to tell him of her progress.
6.3
5-8
Keywords: Boarding schools -- Fiction; Letters -- Fiction; Orphans -- Fiction; Schools -- Fiction; Letters -- Fiction; Orphans -- Fiction; Private schools -- Fiction; School stories